The Psychological Empowerment Potential of Solutions Journalism: Perspectives from Pandemic News Users in the UK. (17th February 2022) - Zhao, Xin; Jackson, Daniel; Nguyen, An
ABSTRACT: Traditional problem-focussed news often cast audiences in passive and reactive ways, which can disempower them from participating in civic life. With influences from positive psychology, solutions journalism (SOJO) is proposed as a way to improve audiences' mental wellbeing and engagement with the news. However, research seldom systematically examines how SOJO psychologically empowers audiences, leaving a gap for a more thorough understanding of the potential of SOJO in fulfilling the democratic role of journalism. Drawing on the theory of psychological empowerment (PE) and through 59 in-depth interviews with members of the public in the midst of the COVID-19 pandemic, we examine UK audience responses to the concept of SOJO. Normatively promising findings emerged from our study. SOJO was considered to be useful in intrapersonal empowerment (i.e., increasing perceived control and self-efficacy), interactional empowerment (i.e., enhancing critical awareness), and behavioural empowerment (i.e., motivating community involvement and coping behaviours). Theoretically, this study establishes a firm connection between SOJO and PE which, we argue, has important implications for journalism's often troubled relationship with civic engagement. As such, we call for a rethinking of the often taken-for-granted problem-focussed news practices.